Giving Birth in the Mountains: Plants and Practices in Reproductive Health of Zapotec Women in Northern Oaxaca - Mahecha-Ruiz, Lindary Camila; Bravo-Avilez, David; Manzanero-Medina, Gladys Isabel; Vázquez Dávila, Marco Antonio; Rendón-Aguilar, Beatriz (Ethnobiology and Conservation, 2024)
Midwives/healers assist women in rural communities in Mexico and use medicinal plants to relieve different conditions related to reproductive health. This knowledge has been passed down and preserved through generations. The aims of the study were: 1) to document the floristic richness of medicinal plants used in the reproductive health of Zapotec women from the Sierra Norte of Oaxaca; 2) to document events, stages, and conditions during reproductive health; and 3) to provide evidence on the continuity of midwifery practices in the region. We interviewed 100 Zapotec women, 11 midwives/healers, the municipal authorities of four municipalities: Tabaá, Yojovi, Solaga, and Analco, and personnel from each health center. We recorded 66 plant species, with cinnamon, avocado, and rue the most mentioned. Asteraceae, Lamiaceae, Poaceae and Fabaceae were the most abundant. We identified five events with different stages/conditions during the reproductive health of women. The number of species mentioned by Analco collaborators differed by age category, indicating a breakdown in traditional knowledge. Multivariate analysis comparing the knowledge of native and introduced species between the collaborators of four municipalities revealed that they were clustered because of the mention of some introduced species (Analco) or because some species were mentioned once (Laxopa). However, the same analysis using native species shows no grouping, suggesting that women share similar knowledge. Traditional midwifery practices and medicinal plants used during the reproductive stage of Zapotec women are still based on native Mexican plants, and their persistent use will depend on the context of each locality and the global medicine system.